Ernährung bei multimorbiden Patienten – Daten oder Meinungen? - Plauth, Mathias (DMW - Deutsche Medizinische Wochenschrift, 2017)
Polymorbidity and old age are rather the rule than the exception in hospitalised patients. Malnutrition is common in such patients and should be identified by appropriate screening and assessment measures in order to devise a nutrition plan and act accordingly. Unlike in the UK or The Netherlands, malnutrition screening and nutrition teams are not mandatory for German hospitals. Malnutrition and, in particular, sarcopenia are indicators of a nutrition associated risk or increased morbidity and mortality. Malnutrition can affect patients of any medical discipline and, therefore, is managed most efficiently by the interdisciplinary and multiprofessional nutrition team. By this approach goal directed nutrition therapy can improve morbidity and mortality of hospitalised patients.
Keywords: Mangelernährung; Screening; Sarkopenie; Ernährungsberatung; Ernährungstherapie; enterale Ernährung; parenterale Ernährung; Ernährungsteam; Ernährungsmedizin